2020
DOI: 10.3390/polym12030606
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Performance of Ultra-Fine Polypropylene Antibacterial Fibers via Melt Electrospinning

Abstract: Polypropylene (PP) fibers are employed commonly as the raw material of technical textiles (nonwovens), and the research focuses on fine-denier fibers and their functionalities. In this work, antibacterial PP masterbatches with different dosage (1–5 wt.%) of nano-ZnO particles as the antibacterial agent were prepared via a twin-screw extruder. The as-prepared PP masterbatches were electrospun on a home-made electrospinning device to afford ultra-fine PP fibers. The morphologies of as-spun ultrathin PP fibers wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 40 publications
0
8
0
1
Order By: Relevance
“…In addition, all typical calcium carbonate reflections are observed on X-ray patterns of nonwoven composite materials, the intensity of which increases as the content of filler increases. The study of samples by IR spectroscopy revealed (Figure 6a), that the spectra of all the samples contain antisymmetric and symmetric stretching vibrations of C-H in methyl (2953 and 2872 cm −1 , respectively) and methylene (2919 and 2840 cm −1 , respectively) groups; bending vibrations of C-H in methyl groups: antisymmetric (1450 cm −1 ) and symmetric (1378 cm −1 ); bending vibrations of C-H bonds in methylene groups: scissoring (1457 cm −1 ) and wagging (1304 cm −1 ) [7,8]. Bands 1219, 1167, 1101, 998, 973, 941, 899, 841, and 808 cm −1 in isotactic polypropylene are called crystallinity bands and belong to isotactic chains of various lengths [42].…”
Section: Structural Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, all typical calcium carbonate reflections are observed on X-ray patterns of nonwoven composite materials, the intensity of which increases as the content of filler increases. The study of samples by IR spectroscopy revealed (Figure 6a), that the spectra of all the samples contain antisymmetric and symmetric stretching vibrations of C-H in methyl (2953 and 2872 cm −1 , respectively) and methylene (2919 and 2840 cm −1 , respectively) groups; bending vibrations of C-H in methyl groups: antisymmetric (1450 cm −1 ) and symmetric (1378 cm −1 ); bending vibrations of C-H bonds in methylene groups: scissoring (1457 cm −1 ) and wagging (1304 cm −1 ) [7,8]. Bands 1219, 1167, 1101, 998, 973, 941, 899, 841, and 808 cm −1 in isotactic polypropylene are called crystallinity bands and belong to isotactic chains of various lengths [42].…”
Section: Structural Analysismentioning
confidence: 99%
“…Polypropylene is a commodity polymer that combines a number of useful properties, i.e., low density, low moisture absorption, mechanical strength, high chemical resistance, and low cost. Fibers and nonwovens based on polypropylene are of considerable practical interest, e.g., in the fields of filtration [ 1 , 2 , 3 ], oil sorption and oil–water separation [ 4 ], protective coatings [ 5 ] and sensors [ 6 ], as well as in medicine and tissue engineering [ 7 , 8 ]. The average diameter of fibers in these materials depends on the production parameters and can vary from a few to dozens of micrometers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have been carried out to improve melt electrospinning technology and thus overcome the limitations caused by the high temperature, high viscosity and/or low conductivity of the polymer melt, with the aim of reducing the fiber diameter [ 22 ]. Microfibers and sub-microfibers have been produced from several polymers (including polyethylene, PP and PLA) using single-fiber melt electrospinning devices and other configurations [ 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Narrower fibers can be produced by integrating a gas stream [ 30 ] or by including additives that increase conductivity and or reduce viscosity [ 18 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…The obtained antibacterial activity is also lasting. Limited by high-temperature MB processing, inorganic nanometals or metal oxides are generally used as antibacterial agents [ 29 , 30 , 31 ], and the silver compounds have especially been proved to be very effective. However, the potential hepatotoxicity of silver is still a concern, and its long-term effects on mammalian cells remain unclear [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%